Analysis of the Application of Virtual Simulation Software in Food Testing Technology Course with Atomic Absorption Spectrum1-- Taking the Example of Determining Calcium in Drinking Water by Atomic Absorption Spectrometry. Issue 1 (March 2021) - Yan, Gu; Wei, Huang
Abstract: Atomic absorption spectrometry is the core content of instrumental analysis and also one of the most commonly used skills in modern detection positions. It can improve the teaching effect to train students on this skill with virtual simulation software. In this project, the experimental group (virtual simulation teaching) and the control group (traditional teaching) were adopted to make a check test in the teaching project of determining calcium in drinking water by atomic absorption spectroscopy, with the purpose of introducing information teaching means and improving teaching quality with simulation software.